2011
DOI: 10.4028/www.scientific.net/amr.243-249.6857
|View full text |Cite
|
Sign up to set email alerts
|

Study on Thermal Environment of Traditional Architecture in Tropic Climate

Abstract: Haikou is located in tropic climates in China. The outdoor environment in summer is too harsh to stay here. However, the traditional architecture, namely arcade, still survives in the severe climate. Its indoor and outdoor parameters of arcade are tested in field to research its thermal environments. The heat stress index is used to study the adaptability mechanism of arcade and local human to hot and humid environment. It proves that the metabolic rate and wind velocity are main and adjustable factors to redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
1
1
0
1
Order By: Relevance
“…The results of this study are in line with the results of previous studies that focused on the application of passive design elements in buildings in different parts of the world [10,11,21,22,28,29]. Thus, we concluded that the current study contributes to the knowledge in this field by evaluating the building performance in the city of Bushehr in Iran, where master builders have used passive architectural elements through in older architecture in order to attain thermal comfort.…”
Section: Classsupporting
confidence: 88%
See 1 more Smart Citation
“…The results of this study are in line with the results of previous studies that focused on the application of passive design elements in buildings in different parts of the world [10,11,21,22,28,29]. Thus, we concluded that the current study contributes to the knowledge in this field by evaluating the building performance in the city of Bushehr in Iran, where master builders have used passive architectural elements through in older architecture in order to attain thermal comfort.…”
Section: Classsupporting
confidence: 88%
“…Results of this study revealed that architectural elements like Transom Ventilation Panels (TVPs) and ornamental windows in all sides of the building could significantly improve indoor ventilation and air change rate [9]. In general, traditional houses in hot-humid areas were constructed to provide maximum thermal comfort with natural ventilation, and to specifically reduce moisture [10][11][12]. In order to use the wind in these regions, buildings have been constructed above the ground to allow the air coming in and out freely.…”
Section: Introductionmentioning
confidence: 99%
“…Sebagai cakupan dari kenyamanan fisik, kenyamanan termal merupakan fokus utama dalam pembahasan berikutnya. Kondisi termal dapat dipengeruhi oleh variabel-variabel iklim seperti; temperatur udara (air temperature), kelembapan udara (humidity) dan pergerakan udara (air movement) (Wang et al, 2011). Menurut Fanger (1973…”
Section: Kenyamanan Termalunclassified